Hubungan Dukungan Ibu dengan Kesiapan Remaja Putri dalam Mengahadapi Menarche - Juwita, Sellia (KESMARS: Jurnal Kesehatan Masyarakat, Manajemen dan Administrasi Rumah Sakit, 2018)
According to the World Health Organization (WHO), adolescents are individuals who are undergoing a period of transition that gradually reaches sexual maturity, changes in the souls of children into adulthood. The changes that occurred at the time of Menarche caused young women to be embarrassed. Therefore, young women need to make adjustments in behavior. The adjustment cannot be done smoothly, especially if there is no support from parents, especially mothers. The role of the mother is very important in the process of growth and development of children, especially during adolescence. Teens begin to recognize the various sexual processes that are happening on the body and soul first through the mother. The design in this research is quantitative analytic, with the population of junior high school girls in Kecamatan Senapelan with total sampling technique, the number of samples 258 people. Data were collected through questionnaires and processed by computerization then analyzed univariat and bivariate using chiquare test. Univariate results in the knowing of girls who get mother support 49.2 percent and who do not get support as much as 57.8 percent, adolescents ready to face menarche 57.4 percent and not ready as much as 42.6 percent. The result of bivariate analysis showed that there was a correlation between mother support with adolescent readiness in facing menarche where p value value less than 0,05. Adolescents with maternal support are more prepared for menarche than those who do not get support. Keywords: Maternal support, readiness, menarche, adolescence